2020
DOI: 10.1093/cvr/cvaa188
|View full text |Cite
|
Sign up to set email alerts
|

Classical monocyte transcriptomes reveal significant anti-inflammatory statin effect in women with chronic HIV

Abstract: Aims During virally-suppressed chronic HIV infection, persistent inflammation contributes to the development of cardiovascular disease (CVD), a major comorbidity in people living with HIV (LWH). Classical blood monocytes (CMs) remain activated during antiretroviral therapy and are a major source of pro-inflammatory and pro-thrombotic factors that contribute to atherosclerotic plaque development and instability. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 82 publications
1
14
0
Order By: Relevance
“…[34] As an example, we applied the classical monocyte transcriptomes (8 subsets) to bulk transcriptomes of sorted classical monocytes from 92 subjects. [7] We found 1 of the CM subsets in all subjects and others at varying proportions ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…[34] As an example, we applied the classical monocyte transcriptomes (8 subsets) to bulk transcriptomes of sorted classical monocytes from 92 subjects. [7] We found 1 of the CM subsets in all subjects and others at varying proportions ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 90%
“…Cell proportions of classical monocytes (CMs, CM1-8) from the present dataset in 92 samples of classical monocyte transcriptomes in women with HIV, CVD, both or neither. [7] CM, classical monocyte; CRT, cholesterol-reducing treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, when we focused specifically on gene functions and pathways that we previously found were dys-regulated in HIV/ART compared with control participants, there was no evidence that they were impacted as a group by atorvastatin. In contrast, a recent retrospective study of HIV+ ART-treated women with subclinical cardiovascular disease reported that treatment with statins for clinical indications was associated with downregulation of inflammatory genes in classical monocytes [ 25 ]. Thus, in HIV/ART participants without clinical indications for statin use, we find no evidence for monocyte gene expression effect of atorvastatin that exceeds random inter-participant and intra-participant variability, or that treatment shifts monocyte gene expression closer towards “normal” patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Statins, widely used in people living with HIV for lipid disorders, have pleiotropic immunomodulatory effects beyond those related to cholesterol lowering, which are mediated by lipid modifications of small signaling molecules [ 20 ]. Statins have been the focus of considerable interest as adjunctive therapy in HIV/ART patients [ 21 25 ]. In vitro , we [ 24 ] and others [ 26 , 27 ] have shown that statins modulate monocyte activation by triggers that contribute to residual immune activation in HIV/ART patients.…”
Section: Introductionmentioning
confidence: 99%